A lógica da descoberta nos jogos digitais - Tonéis, Cristiano Natal (2010)
The present study into the perspective of development the reasoning logicalmathematical by means of the ontological structures in the digital games happens on a specific modality of digital games that present many structures narratives, and its structural development in the form of logical puzzles, practical, related with the idea Greek of mathéma. The methodology has used combines the conceptual efforts in philosophy of the logical positivism, hermeneutic phenomenology, the pragmatic logic, the genetic epistemology, Ethnomathematics and games practical theory, showing that puzzles in the digital games constitute in cognitives structures of high value for the promotion and production of the knowledge, practical and scientifical, as well as achievement and promotion of its structures narratives that they culminate in uncurling of an interactive history. The research takes as example shape the game Myst, establishing it as descriptionconceptual reference that allows the integration of new forms to stimulate and to support the apprehension of logical-mathematicians knowledge, being assumed and demonstrating that to the reasoning logical-mathematician, organized in the form of puzzles, structured in a way thought oncologic. Thus, it shows the organization of new and versatile forms for the modeling, symbolization, analysis, exploration, conjecture and demonstration of the knowledge mathematician, in the playful-cognitive form of puzzles into the immersive digital universes, more recently assigned as metaverses. From then on, the research demonstrates the theoretician-pragmatic value of creation and organization of digital games that can serve to advancement human culture, in reference the promotion of the human subjectivity in the culture, as well as in the structuralization and equilibration of structures logical-cognitives in immersive experience through the adventure games and by means its puzzles. Thus, we indicate the value of use of the digital games (metaverses) as complementary structure for the development of critical abilities in the citizen in a process of continuous education, as well as in its aspects of widening of the mathematical understanding as logical as cultural, where from universalisation and generalization the experience into the puzzles in metaverses. We show the results of an experience with children in school age, which the use of the game model promoted an increment in his general cognitives abilities and change the form they see the world and solving problems that demand an attitude logical-mathematics. Students not only must use multimedia to learn, but they can also use it to communicate their understanding of the subject to those around them. Virtual reality has the potential to move education from its reliance on books to experiential learning in naturalistic settings. The research culminates with the proposal of a heuristic for the resolution of problems, which as children as adult chance over a new species of epistemologists that, from the experience in the digital games, argue in to think the forms of thinking , or rethink, look at problems in many different ways mathéma by the resolution of puzzles